Method for repairing ZCuPb10Sn10 lead bronze through laser additive and application

Through laser additive repair technology, optimized alloy powder A and laser cleaning technologies, the problem of wear of ZCuPb10Sn10 lead bronze alloy parts is solved, achieving high mechanical properties and wear resistance after repair, and improving repair efficiency and safety.

CN119800348AActive Publication Date: 2025-04-11WUHU STATE-OWNED FACTORY OF MACHINING
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411889199.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In aviation applications, ZCuPb10Sn10 lead bronze alloy has abrasive particles with lower hardness than the abrasive particles in the airflow, resulting in wear and performance reduction, increasing the safety risks of aircraft. At the same time, existing repair technologies cannot effectively repair parts where shapes are damaged.

Method used

A laser additive repair method is adopted to repair it using alloy powder A, in which Sn11%-13%, Ni1.8%-2.2%, Al4%-6%, O0.01%-0.025%, and the rest is Cu. Through laser cleaning, non-destructive detection and multi-layer repair layer stacking technology, the good bonding of the repair layer and the substrate and high wear resistance are ensured.

Benefits of technology

The mechanical properties after repair and airflow erosion resistance are achieved better than the matrix, reducing repair cycles, improving repair efficiency, and ensuring high quality and safety of the repair layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800348A_ABST
    Figure CN119800348A_ABST
Patent Text Reader

Abstract

The invention relates to the field of copper alloy laser additive repair, and particularly discloses a method for laser additive repair of ZCuPb10Sn10 lead bronze and application of the method. A to-be-repaired area is cleaned, an oxide layer is removed from the end face of the to-be-repaired area on a base body through laser cleaning till the surface is clean and metallic luster is exposed, and the to-be-repaired area is cleaned through acetone; performing nondestructive testing on the to-be-repaired area, determining the position of the repaired area according to a nondestructive testing result, and performing laser additive repairing on the repaired area by using the alloy powder A; the alloy powder A comprises the following components in percentage by weight: 11%-13% of Sn; 1.8%-2.2% of Ni; 4%-6% of Al; 0.01%-0.025% of O and the balance Cu. The novel alloy powder A used for laser additive repair is developed and can be prepared on a large scale, the safety of the alloy powder A in the large-scale preparation and using process is guaranteed by preferably increasing the content of Ni and Al elements and removing the Pb element, and meanwhile the wear resistance of the repaired surface and the bonding performance between a base body and an additive repair layer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a repair method, in particular to a method and application of laser additive repairing ZCuPb10Sn10 lead bronze, belonging to the field of laser additive repairing of copper alloys. Background Art

[0002] ZCuPb10Sn10 is a cast bronze alloy with good lubrication, wear resistance and corrosion resistance. It can withstand cutting processing well and is widely used in sliding bearings with high surface pressure and side pressure. Lead bronze aircraft parts made of ZCuPb10Sn10 alloy are eroded by airflow during use, resulting in cross-sectional wear. Since the hardness of ZCuPb10Sn10 alloy material is lower than the abrasive particles in the airflow, ZCuPb10Sn10 alloy parts are worn during use, and their performance is reduced, increasing the safety risk of the aircraft. At the same time, a large number of these parts are used on aircraft, and the damage to these parts is in batches. The cost of replacing them with new ones is high, and the procurement cycle is long, which seriously affects production efficiency. The repair layer obtained by brush coating and thermal spraying technology is a mechanical bond, not a metallurgical bond, and is only suitable for surface shape repair, but cannot repair damaged parts. The brazing joint formed by brazing repair has a relatively small bonding strength. The heat-affected zone (>1.5mm) of fusion welding repairs such as argon arc welding is relatively large. In comparison, laser additive repair has high energy density, small heat input, fast crystallization speed, fine grains in the repair layer, and good mechanical properties of the repair layer, and is gradually being used in the repair of damaged aviation parts.

[0003] At present, the research on ZCuPb10Sn10 laser additive technology is mainly focused on the preparation of laser additive repair coating on ZCuPb10Sn10 alloy. The master's thesis of North University of China "Study on the Microstructure and Properties of Cu15Ni8Sn Alloy Coating Repaired by Laser Additive Repair on CuPb10Sn10 Alloy Surface" introduced the preparation of laser additive repair coating on CuPb10Sn10 alloy. First, the powder of its laser additive repair is made of Cu single powder, Ni single powder, and Sn single powder through mechanical mixing. The method of preparing alloy powder is difficult to carry out large-scale and stable production, and it is difficult to carry out engineering applications; second, its laser additive repair coating only detects the friction and wear performance of the coating and the substrate, and does not detect and compare the bonding performance of the coating and the substrate. The room temperature tensile performance of the laser additive repaired joint is determined by the bonding force between the additive repair zone, the heat affected zone, and the substrate. The important application indicator of laser additive repair in aviation maintenance is whether the room temperature tensile performance after repair meets the performance.

[0004] The Pb element in the ZCuPb10Sn10 alloy is very easy to evaporate at high temperatures and is toxic. If it is prepared into powder and laser additive repair is carried out, it is easy to cause harm to human health. At the same time, the alloy powder of the same material is difficult to ensure that the mechanical properties and wear resistance of the ZCuPb10Sn10 alloy after wear repair meet the use requirements; based on personnel health and performance requirements after repair, this patent provides a laser additive repair method suitable for ZCuPb10Sn10 alloy, so that the mechanical properties and airflow erosion resistance of aircraft ZCuPb10Sn10 alloy parts after laser additive repair are better than those of the matrix. Summary of the invention

[0005] In view of the problems in the prior art, the present invention provides a method and application of laser additive repair of ZCuPb10Sn10 lead bronze.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for laser additive repair of ZCuPb10Sn10 lead bronze, the method comprising the following steps:

[0008] Step 1: Clean the area to be repaired. Use laser cleaning to remove the oxide layer on the end surface of the area to be repaired on the substrate until the surface is clean and the metallic luster is exposed. Use acetone to clean the area to be repaired.

[0009] Step 2: Perform nondestructive testing on the area to be repaired, determine the location of the repair area based on the results of the nondestructive testing, and cover the part of the area to be repaired other than the repair area with aluminum foil;

[0010] Step 3: Use alloy powder A to perform laser additive repair on the repair area;

[0011] The weight percentage of each component in the alloy powder A is Sn 11%-13%; Ni 1.8%-2.2%; Al 4%-6%; O 0.01%-0.025%, and the rest is Cu.

[0012] Optionally, during the laser additive repair process, the laser cladding head is tilted 8-10 degrees based on a plumb line of the repair area.

[0013] Optionally, the process parameters in the laser additive repair process are:

[0014] 99.999% high-purity argon is used as the protective carrier gas of alloy powder A, the gas flow rate of the protective carrier gas is 18-20L / min, the laser power is 1500-1600W, the laser cladding scanning speed is 8-10mm / s, the laser spot diameter is 1.2mm, the powder feeder speed is 0.8-1r / min, the powder feeding gas flow rate is 4-6L / min, and the overlap rate is 40%-50%.

[0015] Optionally, during the laser additive repair process, the repair area is repaired by stacking multiple repair layers in sequence, and after each layer is repaired, the next layer is repaired by laser additive when the temperature between the layers drops below 40°C.

[0016] Optionally, during the laser additive repair process, after repairing one layer, laser cleaning is used to clean the surface of the repair layer to remove the oxide layer until the surface of the repair layer is clean and reveals a metallic luster, and acetone is used to clean the repair layer before laser additive repair of the next layer.

[0017] Optionally, after the repair area is repaired, it is trimmed to reach a preset standard size.

[0018] Optionally, the repaired area after the size modification is qualified if no cracks are found using fluorescent testing.

[0019] Optionally, the alloy powder A is prepared by a gas atomization method or a plasma rotating electrode method, and the powder particle size of the alloy powder A is 50μm-150μm, wherein 48μm≤D10≤55μm, 90μm≤D50≤110μm, and 120μm≤D90≤150μm.

[0020] Optionally, after the alloy powder A is prepared, the sample substrate is repaired using the alloy powder A, and the bonding performance between the repair layer and the substrate and the friction and wear performance of the repair layer are tested. The repair can be carried out only after both properties meet preset standards.

[0021] Optionally, a method for laser additive repair of ZCuPb10Sn10 lead bronze is also provided for application in the field of ZCuPb10Sn10 lead bronze repair.

[0022] Beneficial effects of the present invention:

[0023] 1. A new type of alloy powder A for laser additive repair has been developed and can be mass-produced. By increasing the content of Ni and Al elements and eliminating Pb elements, the safety of alloy powder A during mass preparation and use is guaranteed. At the same time, the wear resistance of the repaired surface and the bonding performance between the substrate and the additive repair layer can be improved.

[0024] 2. During the repair process, small-diameter spot and high-energy-density laser additive repair are used to effectively reduce the heat-affected zone, reduce deformation, and improve the quality of repair.

[0025] 3. During the repair process, laser cleaning is used to clean the interlayer slag, which effectively reduces metallurgical defects and reduces damage to the part matrix compared to mechanical cleaning.

[0026] 4. The repair cycle is greatly reduced, the cycle is greatly shortened, and the repair efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0028] Figure 1 This is a top view of the sampling of the tensile specimen for laser additive repair according to the present invention.

[0029] Figure 2 This is a stereoscopic diagram of sampling of the tensile specimen for laser additive repair according to the present invention.

[0030] Figure 3 This is a friction and wear specimen repaired by laser additive manufacturing according to the present invention.

[0031] Figure 4 This is a process flow chart for preparing alloy powder A of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The substrates described in the following embodiments are all ZCuPb10Sn10 alloys.

[0034] See also Figure 1-4 As shown, a method for laser additive repair of ZCuPb10Sn10 lead bronze, the method comprising the following steps:

[0035] Preparation of alloy powder A:

[0036] The amounts of the components in the alloy powder A are Sn 11%-13% by weight; Ni 1.8%-2.2%; Al 4%-6%; O 0.01%-0.025% and the rest is Cu. The alloy powder A is prepared by a gas atomization method or a plasma rotating electrode method, and the powder particle size of the prepared alloy powder A is 50μm-150μm, wherein 48μm≤D10≤55μm, 90μm≤D50≤110μm, and 120μm≤D90≤150μm.

[0037] At present, the failure mechanism of lead bronze aircraft parts made of ZCuPb10Sn10 alloy in the field of aviation maintenance is mainly friction and wear. Therefore, after the preparation of alloy powder A, the sample matrix is ​​repaired with alloy powder A, and the bonding performance of the repair layer and the matrix and the friction and wear performance of the repair layer are tested. The repair can only be used after both properties meet the preset standards. If one or two properties in the test results fail to meet the preset standards, alloy powder A needs to be re-prepared.

[0038] Preferably, the weight percentage of each component is Sn12%, Ni2.0%, Al4%, O0.02%, and the rest is Cu, and the alloy powder A is prepared by gas atomization method. The prepared alloy powder A is used to perform laser additive repair on the sample matrix to obtain the following figure Figure 1 The room temperature tensile specimens shown and Figure 3 The friction and wear specimens shown were then subjected to tensile test and friction and wear test respectively on the room temperature tensile specimens and friction and wear specimens.

[0039] Sample Type Tensile strength(MPa) Friction coefficient Sample matrix 260 0.18 Test specimen 239.2 0.10

[0040] After performance comparison, alloy powder A was used for laser additive repair, and the tensile strength of the repaired sample reached 92% of the sample matrix. At the same time, the friction coefficient of the repair layer was smaller than the friction and wear coefficient of the sample matrix, so the wear resistance of the repair layer was better than that of the matrix.

[0041] The preset performance standard is that the bonding performance after repair (i.e. the tensile strength of the repaired sample) is not less than 90% of the sample matrix, and the wear resistance is better than the matrix. The alloy powder A prepared by the above method meets the requirements for laser additive repair and can be mass-produced for subsequent matrix repair.

[0042] The preparation process of alloy powder A is as follows Figure 4 As shown, formulate the technical indicators of the repair powder → prepare the powder → laser additive repair test → laser additive repair material level performance test. If the mechanical properties meet the use requirements, continue with the following product repair. If not, reformulate the powderization and repeat the steps in this process flow until the material level performance of alloy powder A meets the use requirements before product repair.

[0043] Clean the area to be repaired. Use laser cleaning to remove the oxide layer on the end face of the area to be repaired on the substrate until the surface is clean and the metallic luster is exposed. Use acetone to clean the area to be repaired. The area to be repaired can be determined by manual identification or by non-destructive testing, and finally determine an area to be repaired that meets the actual repair needs.

[0044] The repair area is subjected to nondestructive testing, and the location of the repair area is determined based on the results of the nondestructive testing, and the part of the repair area other than the repair area is covered with aluminum foil. Accurately determining the location of the repair area in the repair area can not only facilitate the inspection of whether the impurities in the repair area are cleaned before repair, but also distinguish other locations that are not repair areas and use aluminum foil for protection to prevent other parts from being damaged by laser irradiation during the repair process.

[0045] The repair area is repaired by laser additive using alloy powder A. The process parameters in the laser additive repair process are: using 99.999% high-purity argon as the protective carrier gas of alloy powder A, the gas flow rate of the protective carrier gas is 18-20L / min, the laser power is 1500-1600W, the laser cladding scanning speed is 8-10mm / s, the laser spot diameter is 1.2mm, and the small-diameter spot high-energy-density laser additive repair effectively reduces the heat-affected zone, reduces deformation, and improves the repair quality. The powder feeder speed is 0.8-1r / min, the powder feeding gas flow rate is 4-6L / min, and the overlap rate is 40%-50%.

[0046] During the laser additive repair process, the laser cladding head is tilted 8-10 degrees based on the plumb line of the repair area.

[0047] Since copper alloy has a high reflectivity to 1080 wavelength laser, the laser cladding head is tilted 8-10 degrees during the laser additive repair process so that the laser will not be reflected vertically and damage the focusing lens.

[0048] During the laser additive repair process, the repair area is repaired in the form of stacking multiple repair layers in sequence. After each layer is repaired, the next layer is repaired by laser additive when the interlayer temperature drops below 40°C. During the repair process, an infrared thermometer is used to detect the interlayer temperature and strictly control the interlayer temperature to avoid interlayer heat accumulation that leads to coarse grains and reduces the performance of the repair layer.

[0049] In the laser additive repair process, after repairing one layer, laser cleaning is used to clean the surface of the repaired layer to remove the oxide layer until the surface of the repaired layer is clean and the metallic luster is exposed, and acetone is used to clean the repaired layer before the laser additive repair of the next layer is performed. The slag between layers is cleaned to effectively reduce metallurgical defects and reduce damage to the part matrix compared to mechanical cleaning.

[0050] After the repair area is repaired, it is trimmed by mechanical processing to reach a preset standard size to meet the use requirements of the part base.

[0051] The repair area after the size modification is qualified if there is no crack using fluorescent testing, thus avoiding the situation where the use is affected due to incomplete repair.

[0052] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for laser additive repair of ZCuPb10Sn10 lead bronze, characterized in that: The method comprises the following steps: Step 1: Clean the area to be repaired. Use laser cleaning to remove the oxide layer on the end surface of the area to be repaired on the substrate until the surface is clean and the metallic luster is exposed. Use acetone to clean the area to be repaired. Step 2: Perform nondestructive testing on the area to be repaired, determine the location of the repair area based on the results of the nondestructive testing, and cover the part of the area to be repaired other than the repair area with aluminum foil; Step 3: Use alloy powder A to perform laser additive repair on the repair area; The weight percentage of each component in the alloy powder A is Sn 11%-13%; Ni 1.8%-2.2%; Al 4%-6%; O 0.01%-0.025%, and the rest is Cu.

2. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 1, characterized in that: During the laser additive repair process, the laser cladding head is tilted 8-10 degrees based on the plumb line of the repair area.

3. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 2, characterized in that: The process parameters in the laser additive repair process are: Argon is used as the protective carrier gas of alloy powder A, the gas flow rate of the protective carrier gas is 18-20L / min, the laser power is 1500-1600W, the laser cladding scanning speed is 8-10mm / s, the laser spot diameter is 1.2mm, the powder feeder speed is 0.8-1r / min, the powder feeding gas flow rate is 4-6L / min, and the overlap rate is 40%-50%.

4. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 3, characterized in that: During the laser additive repair process, the repair area is repaired in the form of multiple repair layers stacked in sequence. After each layer is repaired, the next layer is repaired by laser additive when the temperature between the layers drops below 40°C.

5. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 4, characterized in that: In the laser additive repair process, after repairing one layer, laser cleaning is used to clean the surface of the repair layer to remove the oxide layer until the surface of the repair layer is clean and the metallic luster is exposed. Acetone is used to clean the repair layer, and then the next layer is repaired by laser additive.

6. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 5, characterized in that: After the repair area is repaired, it is trimmed to reach a preset standard size.

7. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 6, characterized in that: The repair area after the size modification is qualified if there is no crack using fluorescent testing.

8. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 1, characterized in that: The alloy powder A is prepared by a gas atomization method or a plasma rotating electrode method, and the powder particle size of the alloy powder A is 50 μm-150 μm, wherein 48 μm≤D10≤55 μm, 90 μm≤D50≤110 μm, and 120 μm≤D90≤150 μm.

9. The method for laser additive repair of ZCuPb10Sn10 lead bronze according to claim 8, characterized in that: After the alloy powder A is prepared, the sample substrate is repaired using the alloy powder A, and the bonding performance between the repair layer and the substrate and the friction and wear performance of the repair layer are tested. The repair can be carried out only after both properties meet the preset standards.

10. A method for laser additive repair of ZCuPb10Sn10 lead bronze as claimed in any one of claims 1 to 9, and its application in the field of ZCuPb10Sn10 lead bronze repair.

Citation Information

Patent Citations

  • Special-purpose alloy powder for repairing archaic bronze chime

    CN101260522A

  • Alloy material applicable to aerospace field and preparation method thereof

    CN103509966A

  • Copper powder for laser cladding of lead bronze workpiece and cladding method

    CN111826548A

  • Method for repairing nickel-aluminum bronze part through laser cladding and product thereof

    CN111850546A

  • Method for reducing porosity of oil-free lubrication bearing by using copper-based alloy powder and laser cladding process

    CN118166348A